Common millennial-scale variability of Antarctic and southern ocean temperatures during the past 5000 years reconstructed from the EPICA Dome C ice core - Masson Delmotte V.; STENNI, Barbara; Jouzel J. (The Holocene, 2004)
Measurements of the two water stable isotopes (dD and d18O) along EPICA (European Project for Ice Coring in Antarctica) Dome C ice core are combined with simple isotopic modelling (distillation models) to reconstruct the variability of both the site temperature (East Antarctica) and the moisture source temperature (nowadays probably the subantarctic Indian Ocean). We discuss the difference between the reconstructed site and source temperature profiles with respect to the initial isotopic data. We show that (i) the early Holocene optimum appears first in Antarctica and 800 years later in the Southern Ocean, and (ii) during the last 5000 years, the site and source temperatures co-vary at the centennial timescale. An 833-year periodicity is observed only on deuterium and site temperature and therefore probably of local origin.